Application of Geophysical Techniques for 3D Geohazard Mapping to Delineate Cavities and Potential Sinkholes in the Northern Part of Kuala Lumpur, Malaysia. (31st December 2013) - Bakhshipour, Zeinab; Huat, Bujang B. K.; Ibrahim, Shaharin; Asadi, Afshin; Kura, Nura Umar
Abstract : This work describes the application of the electrical resistivity (ER) method to delineating subsurface structures and cavities in Kuala Lumpur Limestone within the Batu Cave area of Selangor Darul Ehsan, Malaysia. In all, 17 ER profiles were measured by using a Wenner electrode configuration with 2 m spacing. The field survey was accompanied by laboratory work, which involves taking resistivity measurements of rock, soil, and water samples taken from the field to obtain the formation factor. The relationship between resistivity and the formation factor and porosity for all the samples was established. The porosity values were plotted and contoured. A 2-dimensional and 3-dimensional representation of the subsurface topography of the area was prepared through use of commercial computer software. The results show the presence of cavities and sinkholes in some parts of the study area. This work could help engineers and environmental managers by providing the information necessary to produce a sustainable management plan in order to prevent catastrophic collapses of structures and other related geohazard problems.